TARGETING TETRASPANIN 7 TO DEVELOP NEW DRUGS FOR OSTEOCLAST-RELATED BONE DISEASES - Kim, Minhee; Lee, Soo Young (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Bone remodeling is essential for bone homeostasis and is controlled by bone-forming osteoblasts and bone-resorbing osteoclasts. Several bone diseases, including osteoporosis, are related to an imbalance of activity between the 2 cell types. Previous results from our group and others have shown that tetraspanin 7 (TSPAN7) plays an important role in cytoskeletal reorganization and bone resorption in osteoclasts. In this study, we investigated the efficacy of TSPAN7 as a potential new drug target for osteoclastrelated bone diseases. METHODOLOGY We constructed soluble cell-permeable TSPAN7-NT and -CT peptide inhibitors, and TSPAN7-Fc fusion protein that consists of the EC2 domain of TSPAN7 and the Fc part of human IgG (hIgG). The effects of TSPAN7 peptide inhibitors and TSPAN7-Fc on osteoclasts were evaluated by TRAP staining assay, actin ring immunofluorescence assay, and bone resorption assay. The bone-protective effect of TSPAN7-Fc was determined with the pathological bone loss models: lipopolysaccharide (LPS) and ovariectomy (OVX) models. The statistical tests used were the student’s 2-tailed T-test and ANOVA. RESULTS In-vitro study showed that both TSPAN7 peptide inhibitors and TSPAN7-Fc inhibited the formation of fully spreading mature osteoclasts with normal actin rings, thereby leading to significantly decreased bone resorption. In addition, mice treated with TSPAN7-Fc were protected against LPSand OVX-induced bone loss. Interestingly, TSPAN7-Fc induced abnormal morphology of osteoclasts in vivo. CONCLUSION Our findings suggest that specific inhibition of TSPAN7 could be used as a novel therapeutic strategy to treat osteoclast-related bone diseases.